MANRELEBBE DALAM TRADISI BUGIS PAGATAN - Sa’adah Erliani; Desy Hidayanti; Maryam Agustina (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
The purpose of this research is to find out the procession of implementing manrelebbe and the social values contained therein. This celebration is held as a form of appreciation for children's efforts to complete reading the Koran. This sacred event is rarely carried out in the Bugis Pagatan environment because some parents prefer to hold a manrelebbe simultaneously held by the TPA where they recite the Koran, so it is feared that this culture will be abandoned. This research is a qualitative descriptive study. Data collection techniques are carried out through observation, interviews and documentation. The results of this study are that in the Bugis Pagatan tribe, religious education for children begins with teaching morals and the Koran. Teaching the Koran is divided into three stages, namely 1. Koran Biccu (small Koran) at this stage parents or grandparents become their Koran teachers at home until the child completes Koran Biccu, 2. after that the child will move up to Koran Loppo (large Koran). ), in this second stage, parents can continue teaching their children until they graduate or hand them over to one of the Quran teachers in the village to complete their children's reading. not only studying with one teacher of the Koran, it could be two or three teachers of the Koran at the same time. Manrelebbe, there are many values that need to be maintained and upheld, namely the value of worship exalting the Koran as a revelation from Allah SAW, the value of respect for the Koran teacher, the value of compassion for children, the value of kinship, the value of mutual cooperation. Manrelebbe, this custom is acceptable considering that there are values of Worship and social values contained in it by using the Ulf rule, that this culture does not conflict with Nash and culture is categorized as 'Urf which contains many benefits. So it can be concluded that the celebration of Manrelebbe (Khataman Koran) is a valid 'urf.